School Leadership in Improving Learning Environment Management: A Case Study at SD Negeri 4 Tekad - Setiawan, Peldi; Aswad, Fatqul Hajar; Siswoyo, Siswoyo (Jurnal Riset Ilmu Pendidikan, 2025)
This study explores the implementation of school leadership in improving the management of the learning environment at SDN 4 Tekad. Using a qualitative descriptive approach, data were collected through interviews, observations, and document analysis. The findings of the study revealed four main aspects of leadership, namely: managing the learning environment for individual and collective development, supervising learning activities, mentoring in school management, and handling challenges in managing the learning environment. The principal demonstrated a participatory and supportive leadership style, with an emphasis on collaboration, academic supervision, and stakeholder involvement. Despite limited resources and varying teacher capacities, adaptive strategies such as informal mentoring and community engagement proved effective. This study emphasizes the importance of context-based transformative leadership in creating a conducive and inclusive educational climate, especially in rural elementary schools.